Soil Erosion and its Effects on Maize Field as Modified by Amendments in Southwestern Coastal Bangladesh - Abdullah Al Shoumik, Baig; Sanaul Islam, Md. (International Journal of Environment, 2020)
The coastal soils of Bangladesh are preferentially dominated by silt content and stressed by salinity (Na+) as well as low humus content . Hence, these soils are moderately to extremely vulnerable to water erosion, which is a major form of land degradation. The aim of this study was to estimate the soil erosion rate from maize fields in the southwestern coastal region. A field experiment was conducted on maize grown field, which is nearly level, moderately saline, and silt dominated coastal land. The plots were amended with inorganic fertilizer, sieved sand, and decomposed cow dung. Each runoff plot was connected to separate reservoirs and was exposed to rainfall. From the erosive rainstorms, representative critical rainfall intensity was determined. The entrapped eroded material in the reservoirs was collected to estimate the loss of soil. The efficacy of the applied amendments was studied in terms of lowering seasonal (maize growth period) soil loss and erosion associated deterioration of relevant soil parameters. This study revealed that CRI was ≥15 mm h-1. The soil loss during the maize growth period from inorganic fertilizer, cow dung, and sand amended runoff plots were 64(±7) t ha-1 y-1, 51(±5) t ha-1 y-1, and 23(±2) t ha-1 y-1, respectively. The changes in soil properties indicated that after initial erosion, vulnerability to further erosion increased.